A Case for Revival of Traditional Earthquake Resistant Structures in Kashmir (International Journal of Innovative Research in Engineering & Management, 2022)
The valley of Kashmir with an area of  222,236 sq Km located in the north of India falls in a very  high seismic hazard zone. Kashmir has a recorded history  of 5000 years and earthquakes form a big part of that  history. The oldest remains of historic buildings are  basically earthquake damaged ruins of temples and ancient  universities. Because of the frequent occurrence of  earthquakes, the people of Kashmir devised methods to  live with the earthquakes. Later medieval structures in  Kashmir show the emergence of one such method of  lightweight construction with a combination of mud and  brick that’s tied together by timber. This way structures  were erected that could withstand earthquakes. This marks  the beginning of a vernacular residential architecture in the  valley of Kashmir that in our time is known as the Dhajji  Dewari. The term “dhajji dewari” is derived from a Persian  word meaning a patchwork quilt wall. This architecture  was developed by using the material that was locally  available making it easily adaptable to the culture, climate  and natural environment of the Kashmir region. This  striking architecture of the Kashmir valley, considered to  be the architectural heritage of Kashmir, has over the last  few decades has been considered as symbolic of poverty  and has been rapidly replaced by the modern brick with  cement-sand mortar form of construction that is  constructed in a way which in the event of a high internist  earthquake could prove disastrous. Present day plan of  structures requires representing maintainability viewpoints  utilizing a day-to-day existence cycle point of view, yet  additionally the early plan stage where tremor activities  have a huge impact concerning the foundational layout. As  of late, the seismic assessment of stone work structures  utilizing full scale component displaying approaches  became well known, by applying execution-based  evaluation methodology through nonlinear static  (weakling) investigation procedures. This street numbers  the approval for these methodologies alluding to two full scale workmanship structures tried under semi static  sidelong stacking and practically obscure in the writing. The test conduct of tried unreinforced workmanship  (URM) and confined masonry (CM) structures is thought  about against the weakling reaction of the relating  computational models. Then, at that point, alluding to  ordinary lodging in southern Europe and its standard plan  with a built-up concrete (RC) structure, the approved  appraisal apparatuses are utilized to assess the quake safe  prospects of URM and CM arrangements, in particular as  far as greatest pertinent ground speed increases. The brick  work arrangements are likewise analyzed as far as  development costs against the RC typology. The  considered examination instruments present a decent  understanding while foreseeing, acceptably, the test  conduct, along these lines having the option to be utilized  in execution-based plan. Regarding the concentrated-on  lodging, the anticipated sucker reactions for the stone work  structures signify ability to oppose quakes sufficiently. These designs permit likewise a tremendous expense  decrease (up to 25%) against the RC, hence seeming, by  all accounts, to be contending choices. However, after the  2005 Kashmir earthquake this method of construction  seemed intriguing to some researchers and for the first time proper researches were conducted on the construction  method which showed very promising seismic resistance  behavior by this construction method. This paper will  attempt to breakdown the findings of those researches and  draw suggestions and recommendations based on those  findings.
Keywords: Kashmir; Dhajji Dewari; Performance; Timber Frame Bracing; Load Bearing Masonry